1992
DOI: 10.1164/ajrccm/145.2_pt_1.412
|View full text |Cite
|
Sign up to set email alerts
|

Serum Procollagen III Peptide Levels in Subjects with Sarcoidosis: A 5-Year Follow-up Study

Abstract: In a prospective study, Type III procollagen N-terminal peptide was measured in the sera of 38 subjects with biopsy-proven pulmonary sarcoidosis at 6-month intervals over a period of 5 yr. The subjects were divided into four groups according to their radiologic presentation and clinical course: Group A (n = 10) subjects with sarcoidosis Type I without radiologic progression over 5 yr; Group B (n = 5) subjects with sarcoidosis Type I with radiologic progression to Stage II or III; Group C (n = 9) subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
1
15
2
Order By: Relevance
“…However, our finding that the serum PICP level in stage III sarcoid patients is not different from that of stage I and II patients ( fig. 2) would deny this possibility, thus paralleling the evidence obtained by us [9] and others [10] for serum PIIINP level. Increased values of PIIINP do not necessarily mean an increased synthetic process, since it is known that not all of the N-terminal peptide of type III procollagen is removed, but it may be cleaved from the extracellular matrix [24].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, our finding that the serum PICP level in stage III sarcoid patients is not different from that of stage I and II patients ( fig. 2) would deny this possibility, thus paralleling the evidence obtained by us [9] and others [10] for serum PIIINP level. Increased values of PIIINP do not necessarily mean an increased synthetic process, since it is known that not all of the N-terminal peptide of type III procollagen is removed, but it may be cleaved from the extracellular matrix [24].…”
Section: Discussionsupporting
confidence: 64%
“…The availability of a radioimmunoassay for the Nterminal procollagen III peptide (PIIINP) [6], a cleavage product of the type III procollagen molecule, makes it possible to demonstrate that PIIINP levels are increased in bronchoalveolar lavage (BAL) fluid [7,8] and in serum [9,10] of patients affected by sarcoidosis. However it is believed that such an elevation represents the expression of granulomata cell hyperactivity, rather than predicting fibrogenic processes.…”
mentioning
confidence: 99%
“…LOW et al [11] found increased concentrations of PIIINP in the BALF of sarcoidosis patients but no correlation of the peptide levels with clinical severity. Serum-or BALF-PIIINP has been reported to be elevated also in various other studies [8,9,12,14,15,29]. O'CONNOR et al [14] concluded that BALF-PIIINP is a poor indicator of the course and prognosis of this disease, and that an increase in BALF-PIIINP levels may reflect increased type III collagen synthesis associated with inflammatory process, rather than development of chronic lung disease.…”
Section: Discussionmentioning
confidence: 86%
“…Several parameters have been thoroughly evaluated to serve as markers for pulmonary fibrosis, e.g. type III procollagen peptide, collagenase, hyaluronan, and fibrinogen and its degradation products [194][195][196][197][198][199]. The problem encountered with this concept is that none of the named markers can differentiate between pathological fibrosis and normal tissue turnover in inflammation, as demonstrated by the fact that some markers correlate with parameters of alveolitis [198], although conflicting results have been obtained in longitudinal studies [196,197].…”
Section: Fibrosismentioning
confidence: 99%